Pharmacokinetics of indinavir/ritonavir (800/100 mg) in combination with efavirenz (600 mg) in HIV-1-infected subjects - Boyd, Mark A; Aarnoutse, Rob E; Ruxrungtham, Kiat; Stek, Jr, Michael; van Heeswijk, Rolf P G; Lange, Joep M A; Cooper, David A; Phanuphak, Praphan; Burger, David M (Journal of acquired immune deficiency syndromes (1999), 2003)
Addition of efavirenz (600 mg) to indinavir/ritonavir (800/100 mg) results in significant decreases in indinavir levels in healthy volunteers. This study evaluated the steady-state pharmacokinetics of indinavir/ritonavir at 800/100 mg twice daily (bid) in combination with efavirenz at 600 mg once daily (qd) in HIV-infected Thai subjects who used this nucleoside-sparing combination in The HIV Netherlands Australia Thailand Research Collaboration 009 study. At week 4 of the study, 12-hour pharmacokinetic profiles for indinavir/ritonavir were obtained for 20 HIV-infected subjects. For efavirenz, the concentrations at 12 hours and 24 hours (Cmin) after dosing were assessed. All subjects (10 males and 10 females) completed the study. The geometric mean area under the concentration versus time curve, Cmin, and maximum plasma concentration of indinavir were 45.7 mg/(L. h) (95% confidence interval [CI], 39.8-52.5), 0.32 mg/L (95% CI, 0.24-0.44), and 11.1 mg/L (95% CI, 9.4-13.0), respectively. A >10-fold variation in indinavir Cmin was observed. All subjects had an indinavir Cmin that was at least comparable with the reported mean population Cmin of indinavir at 800 mg thrice daily without ritonavir (0.15 mg/L). The geometric mean concentration at 12 hours and Cmin of efavirenz were 3.1 mg/L (95% CI, 2.5-3.7) and 2.1 mg/L (95% CI, 1.6-2.6), respectively. Despite the known pharmacokinetic interaction between efavirenz and indinavir/ritonavir, the combination of indinavir/ritonavir at 800/100 mg bid and efavirenz at 600 mg qd results in adequate minimum concentrations of both indinavir and efavirenz for treatment-naive patients.